2010
DOI: 10.1074/jbc.m110.101147
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Up-regulates MicroRNA-26a and Induces Human Airway Smooth Muscle Hypertrophy by Suppressing Glycogen Synthase Kinase-3β

Abstract: Airway smooth muscle hypertrophy is one of the hallmarks of airway remodeling in severe asthma. Several human diseases have been now associated with dysregulated microRNA (miRNA) expression. miRNAs are a class of small non-coding RNAs, which negatively regulate gene expression at the post-transcriptional level. Here, we identify miR-26a as a hypertrophic miRNA of human airway smooth muscle cells (HASMCs). We show that stretch selectively induces the transcription of miR-26a located in the locus 3p21.3 of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
157
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(165 citation statements)
references
References 70 publications
5
157
1
2
Order By: Relevance
“…Some of the differentially expressed 28 miRNAs are known to be involved in inflammatory lung diseases and PAH. For example, miR-126, -21, and -26a are important in asthma (17,18,21); let7d, miR-21, -155, and -29 are important in IPF (26); and miR-146a, -155, -21, -25, and -26a are important in PAH (14). Here, we found that expression of each of these miRNA was significantly changed by sevoflurane anesthesia; therefore, sevoflurane anesthesia may affect lung diseases such as asthma, IPF, and PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the differentially expressed 28 miRNAs are known to be involved in inflammatory lung diseases and PAH. For example, miR-126, -21, and -26a are important in asthma (17,18,21); let7d, miR-21, -155, and -29 are important in IPF (26); and miR-146a, -155, -21, -25, and -26a are important in PAH (14). Here, we found that expression of each of these miRNA was significantly changed by sevoflurane anesthesia; therefore, sevoflurane anesthesia may affect lung diseases such as asthma, IPF, and PAH.…”
Section: Discussionmentioning
confidence: 99%
“…The pSilencer 4.1-CMV miR-26a expression construct was prepared as described previously (14). Mouse GSK-3␤ cDNA 3Ј-UTR was synthesized and cloned into pcDNA 3.1D/V5-His-TOPO vector (Invitrogen) according to the manufacturer's instructions.…”
Section: Construction Of Expression Plasmids-mentioning
confidence: 99%
“…Real-time Reverse Transcription-Polymerase Chain Reaction (RT-PCR) Expression Analysis-Real-time RT-PCR assays were performed as described earlier (14). The amount of amplified transcripts (2 Ϫ ⌬⌬CT ) was estimated by the comparative CT (⌬ CT ) method and normalized to an endogenous reference (GAPDH) relative to a calibrator.…”
Section: Construction Of Expression Plasmids-mentioning
confidence: 99%
See 2 more Smart Citations